Evolution and functional diversity of the Calcium Binding Proteins (CaBPs) - Haynes, Lee P.; McCue, Hannah V.; Burgoyne, Robert D. (Frontiers in Molecular Neuroscience, 2012)
The mammalian central nervous system (CNS) exhibits a remarkable ability to process, store and transfer information. Key to these activities is the use of highly regulated and unique patterns of calcium signals encoded by calcium channels and decoded by families of specific calcium-sensing proteins. The largest family of eukaryotic calcium sensors are those related to the small EF-hand containing protein calmodulin (CaM). In order to maximise the usefulness of calcium as a signalling species and to permit the evolution and fine tuning of the mammalian CNS, families of related proteins have arisen that exhibit characteristic calcium binding properties and tissue-, cellular- and sub-cellular distribution profiles. The Calcium Binding Proteins (CaBPs) represent one such family of vertebrate specific calmodulin like proteins that have emerged in recent years as important regulators of essential neuronal target proteins. Bioinformatic analyses indicate that the CaBPs consist of two subfamilies and that the ancestral members of these are CaBP1 and CaBP8. The CaBPs have distinct intracellular localisations based on different targeting mechanisms including a novel type-II transmembrane domain in CaBPs 7 and 8. Recent work has led to the identification of new target interactions and possible functions for the CaBPs suggesting that they have multiple physiological roles with relevance for the normal functioning of the CNS.